1782 N.C. Sess. Laws 413 - (:unkn) unknown (My University, 1782)
Created a draft for the Continental Army. Subject to the draft were "all the inhabitants . . . between the ages of sixteen and fifty." To prevent the widespread community practice of filling draft ranks with the most vulnerable and least motivated, the act specified that "no British or Hessian deserter who hath not been a resident of this State twelve months, or orphan or apprentice under eighteen years of age, Indian, sailor or negro slave, shall be received as a substitute for any class volunteer or draft whatever."
Keywords: MILITIAS